2019
DOI: 10.1037/tep0000212
|View full text |Cite
|
Sign up to set email alerts
|

Beyond English only: Addressing language interpretation in professional psychology training.

Abstract: Professional guidelines direct that psychologists working with clients with limitedEnglish proficiency should involve an interpreter if a mental health professional fluent in the client's language is unavailable. However, complexities of interpreted therapy require training.We describe nine relevant areas of trainee skill acquisition and also surveyed 102 multicultural course instructors in APA-accredited psychology programs regarding current professional training. Only 55 (54%) instructors reported providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Enhancing training for delivering BH care with IS is imperative to ensure that patients with LEP have access to the care they deserve. Previous studies highlighted the need for greater training in IS for predoctoral BH trainees, focusing on the classroom (Frandsen et al, 2019; Rozas et al, 2022). We extend this recommendation to applied clinical training and encourage training directors to increase the scope of training for delivering BH services with IS in clinical practicum sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Enhancing training for delivering BH care with IS is imperative to ensure that patients with LEP have access to the care they deserve. Previous studies highlighted the need for greater training in IS for predoctoral BH trainees, focusing on the classroom (Frandsen et al, 2019; Rozas et al, 2022). We extend this recommendation to applied clinical training and encourage training directors to increase the scope of training for delivering BH services with IS in clinical practicum sites.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of BH care delivered with IS varies based on the training and skill of the BH provider as well as the interpreter (Paone & Malott, 2008). However, utilizing IS remains an underdeveloped aspect of clinical training for BH professionals that often occurs only postlicensure (Costa, 2017; Frandsen et al, 2019; Searight & Searight, 2009). For example, Frandsen et al (2019) reported that 38% of American Psychological Association-accredited doctoral programs failed to offer any training in IS.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Disparities in receiving mental health care may further lower numbers of African American and Latinx clients (and all People of Color), further underrepresenting them in a research field dedicated to clinical samples (Alegría et al, 2008;Coker et al, 2016;Cook et al, 2014Cook et al, , 2017Holden & Xanthos, 2009). Finally, in the case of many Latinx-focused topics, there is a clear need for bilingual researchers and clinicians, language interpreters, and high-quality translated/field-tested assessment measures (Case & Smith, 2000;Frandsen et al, 2019). This would likely also be the case for Asian Americans samples, were it not for the disproportionately high numbers of college students, presumably with higher acculturation levels.…”
Section: Discussionmentioning
confidence: 99%